2015
DOI: 10.1002/wmh3.169
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Safe Crack Use Kit Distribution from a Public Health Perspective

Abstract: This paper examines the policy of safer crack use kit (SCUK) distribution within the city of Winnipeg, Canada. Publicly funded, SCUK distribution policy has been a contested topic throughout Canada, despite evidence that crack users represent some of the most marginalized members of society. Using the four pillars approach to drug policy as a guideline, the balance of allocation of resources for harm reduction is critiqued. Harms associated with crack use are broadly categorized as being associated with method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…One practical example could be to enhance access to sterile injecting equipment among people who inject drugs in LAC, given previous research indicating inadequate syringe exchange program coverage in the region . The dissemination of ‘safe’ stimulant smoking kits could also facilitate less risky use patterns and referrals to appropriate professional support among sub‐populations such as MCSM .…”
Section: Discussionmentioning
confidence: 99%
“…One practical example could be to enhance access to sterile injecting equipment among people who inject drugs in LAC, given previous research indicating inadequate syringe exchange program coverage in the region . The dissemination of ‘safe’ stimulant smoking kits could also facilitate less risky use patterns and referrals to appropriate professional support among sub‐populations such as MCSM .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, crack-related harm reduction strategies have primarily been implemented in Canada (Fischer et al, 2016; Tapper et al, 2023), with the most widespread programmes promoting and distributing safer smoking supplies (e.g. pyrex pipes, mouthpieces) in ‘safer crack kits’ (Bergen-Cico and Lapple, 2015; Miskovic et al, 2018; Ivsins et al, 2011). Despite successful efforts there, crack intervention and prevention strategies are rare in Latin America (Domanico and Malta, 2012), although recently there has been an increasing presence of harm reduction programmes, including the use of virando (crack cocaine rock heated with boric acid to create a powder that can be snorted) in Brazil (Almeida et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The kits are provided by harm reduction programmes dedicated to people who use drugs. Following these new public health measures, studies reported decreases in sharing practices and increases in individual interventions with PWSC (Bergen-Cico & Lapple, 2015;Leonard et al, 2008). However, research has also pointed to persisting high prevalence of crack-smoking equipment sharing, even in areas where safer cracksmoking equipment was available (Fischer et al, 2010;Fischer, Cruz, Bastos, & Tyndall, 2013 ;Ti et al, 2011;Ivsins, Roth, Nakamura, Benoit, & Fischer, 2011;Leonard et al, 2008;Roy & Arruda, 2015).…”
Section: Introductionmentioning
confidence: 99%